Pesantrenpreneur; Strategi Alternatif Konstruktif Pendidikan Kemandirian Ekonomi Santri (Studi Lapangan di Pondok Pesantren Riyadlul Jannah Pacet Mojokerto) - Dofiri, Dhoqi; Istianah, Istianah (LPPM Institut Pendidikan Nusantara Global, 2024)
The approach used in this research is a qualitative approach with descriptive research type. Based on the research that has been carried out, it is concluded that alternative strategies in building the economic independence of students at the Riyadlul Jannah Pacet Islamic Boarding School are carried out using several empowerment models, including; First, the model for economic empowerment of students by fostering the potential/intellectual development of students, Second, the model for empowering students through activity programs launched by the Entrepreneur Islamic Boarding School, Third, the Model of empowerment through Social and Moral. Referring to the three empowerment models above, economic development of santri through PesantrenPreneur at STIES Riyadlul Jannah, PP. Riyadlul Jannah Pacet Mojokerto is the first step to build the economic independence of Islamic boarding school students by utilizing Islamic boarding school students as objects for sharia business management.